Plan estratégico del subcentro de salud rural nuevo zapotal área 5 del cantón Ventanas, año 2013-2017. - Santamaría Alarcón, Nelly Estefanía (2014)
The present research was to develop a Strategic Plan of Rural Health Subcentro Zapotal New Windows Canton Area 5 Year 2013-2017 to improve the delivery of health services that are provided there and guarantee the health of members of this community, it was necessary to make a diagnosis of the current situation on the process of planning and organizing Subcentro. Study results showed that priority is to design a strategic plan that allows better organize the staff, and that it can properly perform its functions, goals, activities and actions to the organization Subcentro settled and thus improve the quality service. Note that currently the Subcentro not have a strategic plan, strategic planning inciting or turn this more effective for that reason the Subcentro should design plans and budgets in the short and long-term operations and capital expenditures, the aims to improve and meet the needs of patients. The study various methods, types, techniques and research tools were applied, which allowed to collect primary and secondary information, data that determined the need to develop the Strategic Plan for Rural Health SubCentre New Zapotal Windows Canton Area 5, considered that the study is very beneficial because it allows strengthening the knowledge, expertise is acquired in the administrative management and public and private management alternatives that are designed and implemented will be for the benefit of society in general, as in this case aspires to have an organized institution, which seeks to satisfy the people and community.